Diagnosis and management of arrhythmias in dogs: A cross‐sectional online survey among Flemish veterinary practitioners. Issue 1 (18th April 2022) - Hellemans, Arnaut; Schittekatte, Mark; Covents, Marc; Smets, Pascale
Abstract: Background: Diagnosis as well as management of arrhythmias in dogs can be challenging for veterinary practitioners. The aim was to describe ECG availability and use, as well as the diagnostic and therapeutic experiences and preferences of Flemish veterinarians regarding cardiac arrhythmias in dogs. Methods: Cross‐sectional online survey among veterinarians in Flanders (Belgium). Results: An ECG device was available for 55 out of 102 respondents (54%) and 41 (43%) claimed to use it in case of arrhythmia suspicion. Insufficient knowledge about ECG interpretation and immediate patient referral upon detection of an abnormal heart rhythm were the most important reasons for not having, or not using, an ECG. About half of the respondents (56%) had never used anti‐arrhythmic drugs in dogs, although only a few reported having had a negative experience. Frequently provided reasons for not using anti‐arrhythmic drugs included insufficient knowledge and a low number of dogs with arrhythmias. Conclusion: Most veterinarians reported having little or no expertise with arrhythmias in dogs. Electrocardiogram availability and use among respondents was moderate and too often restricted by insufficient ECG interpretation skills. Continued efforts are needed to increase the confidence and knowledge of veterinarians about arrhythmias in dogs.